Academic Procrastination in Children and Adolescents: A Scoping Review - Marcela Paz González-Brignardello; Angeles Sánchez-Elvira Paniagua; M. Ángeles López-González (MDPI AG, 2023)
Academic procrastination is a persistent behavior in students' academic development consisting of postponing or delaying the completion of necessary tasks and having a deadline for completion, which is associated with detriment in performance, school dropout, and loss of student well-being. The largest body of existing knowledge on this behavior comes from studies conducted with university students, although it is necessary to deepen the findings obtained at lower educational levels. The aim of this work has been to carry out a scoping review of the empirical publications focused on academic procrastination in children and adolescents. The inclusion and exclusion criteria are detailed following the general guidelines of the Joanna Briggs Institute. However, some modifications are incorporated in the flowchart to guide the review sequence. The search was conducted in eleven thematic (ERIC, MedLine, Psychology and Behavioral Sciences Collection, PsycINFO, PubPsych, and Teacher Reference Center) and multidisciplinary databases (Academic Search Ultimate, E-Journals, ProQuest, Scopus, and Web of Science) to identify relevant publications up to 2022, including grey literature. Out of the initial 1185 records screened, a total of 79 records were selected. The search results included a total of 79 records. The most used assessment instruments, the most studied variables, and the type of design and sources of information used in the selected studies are detailed. Cultural aspects that open new lines of future research are identified.